Segregasi Etnis dalam Perkembangan Kota Manggar, Belitung Timur, pada Abad 19 Hingga Abad 20 - Aryandini Novita; M Nofri Fahrozi; Ari Mukti Wardoyo Adi (Badan Riset dan Inovasi Nasional (BRIN), 2022)
Several cities in Indonesia that was built and developed during the colonial era can be categorized as planned cities and grew due to industrial and mining activities. Manggar is a city that grew due to tin mining activities on the east of Belitung Island. This paper will examine the cityscape of Manggar which developed from a simple settlement into a complex settlement. In addition, this paper will also discuss ethnic segregation in Manggar which is one of the characteristics of the city that grew in the colonial era. The source of the data in this article is the result of archaeological research conducted by the Archaeological Center of South Sumatra in 2021. This research compared archaeological data with historical data together with old maps. The results of the analysis showed that Manggar had four phases of development between the early nineteenth and twentieth centuries. In addition, there is also a clear pattern of separation between settlement of one ethnicity with the other ethnicities scattered in Manggar City. The separation of these settlements was a manifestation of the policy of the Dutch East Indies Government issued in 1854 regarding the stratification of social classes based on ethnic groups.